The antimicrobial activities of fig (Ficus carica L.) leaves extract against Staphylococcus aureus and Escherechia coli - Ali, Amirah Nadiah; Salleh, Mohd Syahmi; Harun @ Ismail, Ahmad Fahmi; Rostam, Muhamad Ashraf (IIUM Press, International Islamic University Malaysia, 2018)
Increasing risk of antibiotic resistance of pathogenic bacteria has led to the exploration of alternative antibiotics derived from leaves of medicinal plants such as the fig (Ficus carica L.). The aim of this study was to determine the antimicrobial activity of the methanolic extract of fig leaves grown under Malaysian tropical environment against pathogenic bacteria linked to antibiotic resistance namely the Staphylococcus aureus and Escherechia coli. The methanolic extraction was performed by using soxhlet apparatus. The disc diffusion method was used to measure inhibition zone diameter on the Mueller-Hinton agar plate. Staphylococcus aureus displayed the highest diameter of inhibition zone against the extract at concentration of 900 mg/ml whilst Escherechia coli displayed the highest diameter of inhibition zone against both the 100% crude extract and 700 mg/ml, respectively. This study therefore highlighted the potential of developing alternative antibiotics derived from the methalonic extract of locally grown fig plant